Stranded Assets, the Social Cost of Carbon, and Directed Technical Change: Macroeconomic Dynamics of Optimal Climate Policy - Frederick van der Ploeg; Armon Rezai (Center for Economic Studies and ifo Institute (CESifo), 2016)
The tractable general equilibrium model developed by Golosov et al. (2014), GHKT for short, is modified to allow for stock-dependent fossil fuel extraction costs and partial exhaustion of fossil fuel reserves, a negative impact of global warming on growth, mean reversion in climate damages, steady labour-augmenting technical progress, specific green technical progress driven by learning by doing, population growth, and a direct effect of the stock of atmospheric carbon on instantaneous welfare. We characterize the social optimum and derive simple rule for both the optimal carbon tax and the renewable energy subsidy, and characterize the optimal amount of untapped fossil fuel.
Keywords: H21; Q51; Q54; 330; social cost of carbon; carbon tax; renewable energy subsidy; general equilibrium; Ramsey growth; capital accumulation; stranded assets; simple rules